PENTINGNYA PEMBELAJARAN BAHASA ARAB SEJAK DINI UNTUK MEMBENTUK DASAR KEAGAMAAN ANAK - Rizky Auliani; Dinil Arifah Nasution; Rhea Aquilla Fawaz; Hilda Zahra Lubis (LPPM Universitas Cipta Mandiri, 2025)
Arabic language learning in early childhood has an important role in forming a solid religious foundation. Arabic is the language of the Qur'an, prayers, and worship, so early introduction can help children understand and recite religious readings well. This study aims to analyze the importance of Arabic language learning as an early foundation in the development of spiritual values and Islamic character in early childhood. By using the literature research method, data is obtained from various sources such as books, scientific journals, and relevant research articles. The results show that early learning of Arabic not only supports children's linguistic abilities, but also strengthens their understanding of Islamic teachings, such as tawhid, morals, and worship obligations. Interactive learning methods, such as playing while learning, storytelling and singing, are effective approaches to increase children's interest in learning. This research recommends the importance of teacher and parent involvement in supporting the Arabic learning process to create a fun and meaningful experience for children.